计算(x^(2n)+x^n+1)(x^(3n)-x^(2n)+1)
1个回答
原式=x^(5n)-x^(4n)+x^(2n)+x^(4n)-x^(3n)+x^n+x^(3n)-x^(2n)+1
=x^(5n)+x^n+1
相关问题
计算:(8x^n+3 + x^n+2) * (-2x^n + 3x^n-1)
利用1/n*(n+1) = 1/n - 1/(n+1)计算1/(x-2)(x-3)-2/(x-1)(x-3)+1/(x-
\求和Sn=1+2x+3x^2+```+(n-1)x^(n-2)+n*x^(n-1)
1X2+2X3+...+n(n+1)+n(n+2)
1X2X3+2X3X4+.+n(n+1)(n+2)
1x2x3+2x3x4+.+n(n+1)(n+2)=?
计算:(1)(m-n)^2*(n-m)^5*(m-n)^5 (2)(-x)^2*x^3+2x^3*(-x)^2-x*x^
x^n-1(3x^n+4x^n+1-5x^n+2)
计算:-4(1/2x-2)+1/3(6x-9);3n-[5n+(3n-1)]
(1-x)Sn=1+2x[1+x+x^2+x^3+…+x^(n-2)]-(2n-1)*x^n;